Avaliação da dureza superficial de resinas compostas para dentes posteriors - Baptista Oertli, Daniela Cahú; Vidal Mesquita, Renata [UNESP]; Machado Salete, Candido Maria [UNESP]; Uchoa, Roseanne; Bráz, Rodivan (My University, 2007)
The aim of this work in vitro was to evaluate the superficial hardness of four resin based composites used for restoration of posterior teeth (Point4/Kerr, Z250/3M Espe, Z100/3M Espe and P60/ 3M Espe). Vickers hardness was obtained using a digital microdurometer (Bueler Micromet 2003), which applied 200 gf (1,96 N) load for 15 seconds. Vickers hardness mean values were: Point 4 (53,7); Z100 (104,7); Z250 (86,9) e P60 (86,1). ANOVA indicated significant difference between these results. Tukey's comparison test showed that Z250 and P60 where not different from each other, although they where different from all the other composites. Therefore, it can be concluded that Z100 had the greatest hardness followed by Z250 and P60 (with the same performance) and Point 4 had the lowest Vickers hardness.
Evaluation of superficial hardness of composite resins indicated for posterior teeth
Keywords: Hardness; Posterior teeth; Resin composite